THE EFFECT OF HUMAN RESOURCES DEVELOPMENTAND WORK ABILITY ON EMPLOYEE PERFORMANCE IN THE DEPARTMENT OF HOUSING AND SETTLEMENTS AREA OF KAUR REGENCY - Merwan Afrizal; Ahmad Soleh; Meiffa Herfianti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This study aims to analyze the effect of human resource development and work ability on employee performance in the Department of Housing and Settlements Area of Kaur Regency. Data collection method is by distributing questionnaires to 43 employees. Data analysis used was quantitative analysis, with multiple linear regression methods, determination test, t test and F test. The results showed that the development of human resources and work ability had a positive and significant effect simultaneously on employee performance in the Department of Housing and Settlement Areas of Kaur Regency.